Evaluation of bud fertility from grapevine varieties cultivated in high altitude region of Santa Catarina - Würz, Douglas André; Canossa, Adrielen Tamiris; Reinehr, Juliana; Allebrandt, Ricardo; de Bem, Betina Pereira; Outemane, Marcus; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2019)
A low bud fertility of grapevines varieties is observed in the high altitude region of Santa Catarina, where variations in productivity create much doubt with regard to wine production. Given this context, the objective of this study was to evaluate the bud fertility of grapevine varieties in the high altitude region of Santa Catarina. This study was carried out in the period of 2016/2017. The shoots and buds were taken from a commercial vineyard, located in the city of São Joaquim. Shoots and buds of Cabernet Sauvignon, Cabernet Franc, Merlot, Chardonnay and Sauvignon Blanc varieties were removed after pruning, performed in August 2017, and 20 shoots of each variety were collected to determine bud fertility. The buds were placed in fitotron in an environment with 60% relative humidity, temperature of 25 °C and 12 hours of light per day with intensity of 300-400 μE m-2 s-1. The buds were classified as fertile or non-fertile according to the presence or absence of inflorescence. For the evaluated grapevines varieties, it was observed a higher bud fertility in the apical position of shoot, and lower bud fertility in the basal position of the shoot. The Cabernet Sauvignon variety showed the lowest bud fertility among the five grape varieties evaluated, while Sauvignon Blanc, Chardonnay and Merlot grape varieties showed the highest bud fertility. Due to the higher bud fertility in the apical position, a long pruning system is recommended for these varieties, aiming to increase the number of clusters per buds, and consequently increase productivity indexes of the vineyards.